Advancing Our Understanding of Culture Mixing. (November 2016) - Hao, Jia; Li, Dongmei; Peng, Luluo; Peng, Siqing; Torelli, Carlos J.
Globalization has rendered culture mixing a pervading and overwhelming phenomenon. Culture mixing refers to the coexistence of representative symbols of different cultures in the same space at the same time. It reflects the new paradigm of polyculturalism in the culture and psychology research. The articles in this issue offer nuanced understandings to features of the culture mixing stimuli, personal and situational factors that affect responses to culture mixing, and the sociocultural and psychological consequences of culture mixing. We discuss how these articles provide a new context that extends existing psychological theories and set the stage for the burgeoning psychological inquiry of culture mixing. Future research is needed to uncover how different cultural elements are mixed and how ecological factors affect responses to culture mixing, to investigate the underlying psychological mechanisms of culture mixing, and use multiple methods at various levels of analysis to uncover the dynamic, interactive culturally mixed processes.